From Fossil Energy to Renewable Energy: Why is Circular Economy Needed in the Energy Transition? - Ishaq, Maryam; Ghouse, Ghulam; Fernández-González, Raquel; Puime-Guillén, Félix; Tandir, Natasa; Santos de Oliveira, Helena Maria (Frontiers in Environmental Science, 2022)
For decades, renewable energy consumption has been presented as the ultimate solution to drastically reduce pollutant gas emissions. However, their production, marketing and, above all, consumption are not entirely climate neutral, so society needs new practices, such as circular energy, to achieve a more efficient energy transition. This study aims at exploring the effects of energy intensity, renewable energy consumption and forestation on CO2 emissions for developed and developing countries over the period of 1980 to 2018. Owing to cross-country income disparity the data categorized into four distinct groups: lower, lower middle, upper middle, and high income. The Pedroni and Fisher-Johnson cointegration procedures are employed for long-run relationship. Results reveal significant long-run association between CO2 emission and its determinants, though, the magnitude of this effect is less substantial, particularly in case of renewable energy consumption and forestation. For all country groups, renewable energy intensity turns out to be the most influential long-run determinant of CO2 emissions. Renewable energy consumption is proven to be second most important long-run determinant of CO2 emissions. In case of forestation, the series is found to be imparting (statistically) significant long-run effects only for lower-middle income countries and for low-and high-income country groups their significance is ignorable.